Quantitative characteristics of mast cells in the course of wound healin in rats with chronic social stress - Makyeyeva, L. V.; Aliyeva, O. G.; Frolov, O. K.; Макєєва, Людмила Валеріївна; Алієва, Олена Геннадіївна; Фролов, О. К. (My University, 2021)
Activation of sympathoadrenal and hypothalamic-pituitary systems under the influence of stress, accompanied by the release of neuromediators and neuropeptides, activation of mast cells producing cytokines, chemokines, etc., leads to the launch of a cascade of pathological processes which indicates that stress can lead to a violation of skin reparation. However, little is known about morphofunctional changes of skin cells under the influence of chronic social stress. The aim of this work was to assess changes in the number of mast cells in the rat skin after the influence of chronic social stress. The research was performed on 20 Wistar male rats aged 12-13 months, weighting 390 -430 g: 1st group – control (n = 10); modelled chronic social stress to the 2nd group (n = 10) by the 3-week social isolation and prolonged psycho-emotional impact. Stress was confirmed in an open field test. A skin flap sized 1*1 cm was excised on the back in the interscapular region on the day of wounding, and days 1, 3, 7, 14, 30 of wound healing. Mast cells were counted in wound surface area sections, selectively stained with toluidine blue. The wound healing process in the skin was characterized by a certain dynamic of mast cells’ number, as key cellular regulators of inflammatory and regenerative processes. In intact skin of the experimental group revealed a ten times exaggeration of mast cells compared to the control. In the control group, the content of mast cells gradually increased over the next 2 weeks and decreased to the initial level on the 30th day. Initial high level of mast cells decreased by 86,8% in experimental rats already on day 1 with a gradual rise in the next 2 weeks and raised by 593% compared to control group at day 30 which is associated with migration of immune-dependent cells as a result of partial removal of the stress response. Активація симпатоадреналової і гіпоталамо-гіпофізарної систем при стресі супроводжується вивільненням нейромедіаторів і нейропептидів, активацією тучних клітин, що продукують цитокіни, хемокіни та ін., призводить до запуску каскаду патологічних процесів, вказуючи, що стрес може призвести до порушення репарації шкіри. Однак у сучасних дослідженнях мало даних про морфофункціональні зміни клітин шкіри під впливом хронічного соціального стресу. Метою даної роботи була оцінка кількісних змін тучних клітин шкіри щурів після впливу хронічного соціального стресу. Дослідження проводили на 20 щурах-самцях лінії Вістар вагою 390 -430 г., віком 12-13 міс.: 1-а група – контроль (n=10); тваринам 2-ї групи (n=10) моделювали стрес 3-тижневою соціальною ізоляцією і тривалим психоемоційним впливом. Стрес підтверджено тестом на відкритому полі. Висікали шкірний клапоть розміром 1*1 см на спині в міжлопатковій ділянці в день нанесення рани і на 1, 3, 7, 14, 30 добу загоєння ран. Тучні клітини підраховували в зрізах взятих області ранової поверхні, селективно забарвлених толуїдиновим синім. Процес загоєння ран у шкірі характеризувався відповідними особливостями динаміки кількості тучних клітин, як регуляторів запальних та регенераторних процесів. В інтактних зразках експериментальної групи кількість тучних клітин була більшою в 10 р., ніж в контролі. Загальновідомі нормальні показники вмісту кількості тучних клітин у контрольній групі поступово збільшувались у наступні 2 тижні та зменшувались до вихідного рівня на 30 день загоєння ран. Початковий рівень тучних клітин у 2й групі знизився на 86,8% вже на 1 день з поступовим підйомом у наступні 2 тижні, проте він не досягав рівня контролю з подальшим підйомом на 593% порівняно з 1ю групою на 30 день, що пов’язано з міграційними процесами імунозалежних клітин як результат часткового зняття стресової реакції.
Кількісна характеристика тучних клітин у процесі загоєння ран у щурів із хронічним соціальним стресом
Keywords: impaired wound healing; inflammatory stage; proliferative stage; remodeling stage; psycho-emotional stress; порушення загоювання ран; стадія запалення; стадія проліферації; стадія ремоделювання; психоемоційний стрес